﻿In vitro antimitotic activity and in silico study of some 6-fluoro-triazolo-benzothiazole analogues - Naresh Podila; Mithun Rudrapal; Subramanyam Sibbala; Atul R. Bendale; Yanadaiah Palakurthi; Molakpogu Ravindra Babu; Kiran Manda; Renzon Daniel Cosme Pecho; Sreelatha Muddisett (Pensoft Publishers, 2023)
In this work, nine 6-fluoro-triazolo-benzothiazole derivatives were prepared and evaluated for in vitro antimitotic activity. In addition, in silico study was also done using tubulin protein (PDB: 6QQN) by molecular docking method. Results revealed that TZ2 and TZ9 were the most active compounds with antimitotic action opposing the standard drug, aspirin. Results of molecular docking exhibited the inhibitory potential of triazolo-benzothiazole against tubulin protein. The mitotic study indicates the efficacy of triazolo-benzothiazole analogues in inhibiting the proliferation of cancer cells either by promoting microtubule formation or affecting microtubules, thereby preventing microtubule breakdown.